2016
DOI: 10.5430/jnep.v7n1p1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different suctioning modalities on physiologic measures and the incidence of ventilator associated pneumonia

Abstract: Objective: To compare physiologic measures and the incidence of ventilator associated pneumonia (VAP) using different modalities of endotrachael tube (ETT) suctioning. Methods: A Quasi-experimental design was used with 80 adults in an intensive care unit. Two modalities of suctioning were compared: 1) not instilling normal saline (NS) into the ETT before suctioning, and 2) instilling NS into the ETT tube before suctioning. The outcome variables were: physiologic measures (heart rate, respiratory rate and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Hussein et al investigated the effect of normal saline serum on VAP and physiological parameters. The findings showed that normal saline effectively increased the incidence of pneumonia (12). Several studies have reported adverse effects of normal saline on physiological parameters and the likelihood of pneumonia in patients undergoing mechanical ventilation (1,12,22,23).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hussein et al investigated the effect of normal saline serum on VAP and physiological parameters. The findings showed that normal saline effectively increased the incidence of pneumonia (12). Several studies have reported adverse effects of normal saline on physiological parameters and the likelihood of pneumonia in patients undergoing mechanical ventilation (1,12,22,23).…”
Section: Discussionmentioning
confidence: 91%
“…In their systematic study by Pinto et al, nurses believed that normal saline diluted the secretions, facilitated the insertion of the catheter into the tracheal tube, stimulated the cough reflex and discharge of secretions, and increased oxygenation (11). The findings of a study showed that the pneumonia rate was significantly higher in patients using normal saline to suction secretions (12). Some studies have indicated that using normal saline during tracheal suction causes hypoxia, high blood pressure, bronchospasm, and the displacement of bacterial colonies and their movement to the lower airways, thereby aggravating hospital-acquired pneumonia (13).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that although normal saline is frequently used in endotracheal intubation, different studies have reported different results on whether or not to use it (8,9). For example, Hussein et al (10) conducted a study entitled "The effect of different suctioning modalities on physiologic measures and the incidence of ventilator-associated pneumonia". In this study, the results showed that the use of normal saline before suction does not cause significant changes in hemodynamic parameters but increases the amount of VAP.…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies evaluated the instillation of NS in adults, to the authors' knowledge and the literature review (Hussein et al, 2017;Alja'afreh et al, 2018), this is the first study that aims to examine the practice of instilling NS prior to endotracheal suctioning in NICUs in Jordan. To date, no studies have explored the nature and extent of this practice.…”
Section: Introductionmentioning
confidence: 99%